Forecast successful prevention of infectious complications in preterm infants - N. V. Gonchar; L. A. Lo Schiavo; A. N. Suvorov; S. G. Grigoriev (Журнал инфектологии, 2016)
The objective was to develop mathematical and statistical models forecast the success of prevention of infectious genesis of complications in premature infants with very low birth weight during the inpatient nursing care when used in programs of the therapy probiotic form based on Enterococcus faecium L3. We proposed the mathematical discriminant model forecast the success of prevention of infectious complications based on observations of 55 premature infants with very low birth weight in the second stage of nursing in a specialized department of pathology of newborn hospital and analysis of outcomes for the formation of infectious complicationsin 51 children. This model is based on the following six symptoms: 1) burdened obstetric and gynecological history mother; 2) the presence of chronic intoxication with the mother; 3) delivery is by caesarean section; 4) of the number of E. coli in the feces of children in real time polymerase chain reaction (relative to the norm values); 5) eosinophilia in the clinical analysis of blood; 6) use as a supplement to the diet of children probiotic liquid form on the basis of E. faecium L3. This model has a sufficiently high information capacity (80.4%) and statistically significant (p<0,01) for the prediction of the success of the prevention of infectious complications in premature infants with very low birth weight.